The vocabulary of righteousness in Martin Luther’s New Testament translations - Jones, HS (Routledge, 2019)
In his first version of the New Testament of 1522, Luther had default translations for each of the principal Greek terms relating to righteousness, but departed from them in ways which reflected his theological views. For example, while his default translation of δίκαιος was gerecht, he used frum or recht in contexts which refer to human goodness or lawful conduct, respectively, rather than to righteousness according to his strict conception of it. Luther thus signalled to the reader/listener, at a lexical level, theological distinctions which, outside the Bible, he could spell out explicitly. Luther repeatedly revised his New Testament translation and, when referring to righteousness, he increased the number of translations based on gerecht (gerecht, gerechtigkeit, gerecht machen/werden/sein) at the expense of those based on rechtfertig (rechtfertig, rechtfertigung, rechtfertigkeit, rechtfertigen). This occurred across different parts of speech, but was particularly marked in the translations of verb phrases meaning ‘to justify/make righteous’, where the fraction of gerecht-based translations rose from zero in 1522 to over three-quarters in 1530. The effect was to unify the language of righteousness and justification: rather than having one word-family, based on gerecht, for righteousness and another, based on rechtfertig, for justification, Luther now used gerecht overwhelmingly for both. This was again a reflection of Luther’s theological views, this time emphasizing the identity between the righteousness of God and the God-given righteousness of mankind.